Using solar energy in Kuwait to generate electricity instead of natural gas - Alhouli, Omar J. M. A. (Kansas State University, 2017)
Solar energy is the energy that is basically obtained from the sun. It is used for purposes of generating electricity by using solar thermal systems of photovoltaic panels. This report discusses the utilization of solar energy in Kuwait for purposes of generating electricity. The report is divided into six chapters. Chapter 1 discusses the introduction, which will be limited to the use of electricity in Kuwait and the possibilities of utilizing solar energy as a renewable source of energy to generate electricity. Chapter 2 discusses the background of the use of solar energy, where the reasons and the advantages of using solar energy are analyzed. Chapter 3 gives an in-depth discussion on solar energy. The generation of electricity from photovoltaic solar panels and solar thermal electricity systems are presented. Chapter 4 discusses the comparison between solar power farm and natural gas with the aid of data from Kuwait. Chapter 5 gives a discussion on the use of solar energy in Kuwait. Chapter 6 includes the conclusions and recommendations for future work.
Keywords: Solar energy; Kuwait